Downmodulation of Regulatory T Cells Producing TGF-β Participates in Pathogenesis of Leprosy Reactions - Gomes de Castro, Katherine Kelda; Lopes da Silva, Pedro Henrique; Nahar dos Santos, Luciana; Leal, Julia Monteiro Pereira; de Pinho Pereira, Mylena Masseno; Alvim, Iris Maria Peixoto; Esquenazi, Danuza (Frontiers in Medicine, 2022)
Leprosy reactions are an acute and systemic manifestation, which occurs suddenly, can be severe and lead leprosy patients to disability. Reactional episodes are observed among half of the multibacillary patients, mainly in borderline lepromatous and lepromatous forms. They may begin at any time during multidrug therapy, and even before the treatment. Physical disabilities, which are the source of extreme suffering and pain for patients, occur in progression of the cellular immune response associated with a reaction and are still poorly understood. Thus, this work aimed to phenotypically and functionally characterize CD4+ and CD8+ Treg cells ex vivo and in response to Mycobacterium leprae (ML). We studied 52 individuals, including 18 newly diagnosed and untreated multibacillary leprosy patients, 19 reactional multibacillary patients (Type I or Type II episodes) and 15 healthy volunteers, included as controls, all residents of the city of Rio de Janeiro. The functional activity and frequencies of these cells were evaluated through multiparametric flow cytometry. In addition, the production of cytokines in supernatant from peripheral blood mononuclear cell cultures was also investigated against ML by enzyme-linked immunosorbent assay. Our results showed a decrease in CD4+TGF-β+ Treg and CD8+ TGF-β+ Treg in leprosy multibacillary patients during both reactional episodes. Alterations in the cytokine profile was also observed in Type II reactions, along with upregulation of IL-17 and IL-6 in supernatant. Thus, our study suggests that downregulation of Treg cells is related with both reactional episodes, improving our understanding of immune hyporesponsiveness in multibacillary patients and hyperesponsiveness in both reactions.